Three-dimensional trace element profile reflecting aging, disease, and frailty - Catrin Herpich; Tom Heinze; Varvara Moskiou; Magdalena Kalymon; Lea Göger; Lea Faust; Kristina Lossow; Ursula Müller-Werdan; Tanja Schwerdtle; Lutz Schomburg; Anna P. Kipp; Kristina Norman (GeroScience, 2026)
Older age combined with chronic disease increases the risk of malnutrition and frailty, impacting disease recovery and overall clinical outcomes. Serum concentrations of several trace elements and their respective biomarkers have not yet been investigated with regard to frailty in older adults with disease, although these patients most likely have an altered trace element profile owing to both inflammatory conditions and inadequate dietary intake. This cross-sectional study investigated trace element profiles in relation to age, disease, and frailty status in geriatric patients ( n = 198) as well as in old ( n = 80) and young ( n = 60) healthy controls. Serum concentrations of iron, zinc, selenium, iodine, copper, and manganese were quantified via ICP-MS/MS, alongside inflammatory markers and functional biomarkers. Analysis revealed distinct trace element profiles in patients compared to healthy controls, with lower manganese, iron, zinc, and selenium, but higher copper and iodine ( p ≤ 0.001). Trace element concentrations were similar in young and older healthy controls. Principal component (PC) analysis identified two profiles. PC1 was negatively associated with age, number of drugs, sex, and inflammation. Only PC2 was associated with anorexia (β = 0.053 ± 0.020; 95% CI 0.015, 0.092; p = 0.007). Furthermore, intake of drugs that affect intestinal trace element absorption was associated with PC2. Our analyses suggest that PC1 might reflect disease/inflammation, and PC2 inadequate trace element supply. These cross-sectional findings suggest that inflammation and inadequate trace element intake, rather than age, significantly influence trace element profiles and contribute to frailty. Trail registration number: DRKS00017090, registered 12.04.2019; DRKS00028105, registered 03.03.2022.